Factors Associated With Delirium in Surgical Intensive Care Unit Patients Treated With Supplemental Melatonin: A Case-Cohort Study. Issue 3 (May 2019) - Cusimano, Joseph M.; Welch, Sarah; Perez-Protto, Silvia; Lam, Simon
Abstract : Objectives: Intensive care unit (ICU) delirium is a common neuropsychiatric syndrome that confers significant morbidity and mortality. Melatonin is an endogenous neurohormone involved with regulating sleep-wake cycles and has been found to be disturbed in ICU delirium. We hypothesized that there are independent factors that predict delirium in a cohort of patients on melatonin in the surgical ICU (SICU). Methods: A retrospective, observational case-cohort analysis of adult SICU patients was conducted. Cases were defined by testing positive on the Confusion Assessment Method for the ICU (CAM-ICU). Delirioprotective and deliriogenic factors were assessed prior to the studied melatonin administration. Results: Forty-one CAM-ICU–positive cases and 59 CAM-ICU–negative controls were included. Higher mean Acute Physiology and Chronic Health Evaluation II scores were associated with delirium in univariable analysis. Stratified analysis found a higher incidence of delirium in baseline CAM-ICU–positive patients who experienced emergency surgery within 24 hours of admission compared with baseline CAM-ICU–negative patients after melatonin administration. Conclusions: This study describes the use of melatonin in the SICU and characterizes the patients who receive it. Further research is needed to determine the role of melatonin in deliriogenesis and to clarify its utility as a delirioprotectant for postsurgical, critical care patients.